Creative Industry in South Baltic Area Region = Sektor kreatywny w regionie Południowego Morza Bałtyckiego - Tomczyk, Monika; Spychalska-Wojtkiewicz, Monika (Zielona Góra: Faculty of Economics and Management Press)
The article presents primary and secondary data collected in research on Creative Industry in South Baltic Region. In the article authors present the wide overview on creative industries in West Pomerania region and give the background on situation of creative industries in South Baltic Area. This region is particularly interesting in research considering the diversity in the development dynamics of the creative sector. In this region there are places leading in the development of the creative sector in Europe, as well as places where this sector is just beginning to develop and take advantage of the prevailing trends.
Keywords: sektory kreatywne; rozwój regionalny; innowacje; przedsiębiorczość; creative industries; regional development; innovation; entrepreneurship